Mundos virtuais na formação do educador: uma investigação sobre os processos de autonomia e de autoria - Backes, Luciana (Universidade do Vale do Rio do Sinos, 2007)
This dissertation consists of the theoretical study chiefly based on the Theory of Biology of Knowing by Humberto Maturana, articulated for future teachers’ living and cohabiting in the Virtual World (Eduverse). So two Complementary Activities have been developed: Learning in Virtual Worlds and Teaching Practice in Virtual Worlds for students in different teaching courses in Universidade do Vale do Rio dos Sinos (UNISINOS), and the Village ‘Learning in Virtual Worlds’ was built. The main investigation focus was studying how autonomy and authorship develop in the teacher education by constructing the Virtual Worlds, whose teaching proposal is based on an interactionist/ constructivist/systemic notion. The methodology of the case study helped in collecting empirical data and articulating these data with the analysis theory. The information sources for this study were a questionnaire, electronic excerpts (AVA-UNISINOS, MSN and Eduverse), and images captured in the Virtual World. Evidences coming out from this in
Keywords: computação; conhecimento; formação; realidade virtual; representação; tecnologia digital; tecnologia educacional; professor; authorship; autonomy; cohabiting virtual digital space; virtual world; teacher education; Ciências Humanas